PERTUMBUHAN DAN HASIL TANAMAN KEDELAI PADA KONDISI CEKAMAN AIR DAN PEMBERIAN MIKOKOMPOS (Growth and Yield of Soybean (Glycine max (L) Merril) Under Water Stress Conditions and Mycocompost Application) - . Buhaira; Nerty Soverda; Ardiyaningsih Puji Lestari; Yudi Achnopa (Bioplantae, 2013)
Thi research was conducted to increase soybean tolerance to drought and soil fertility by applying compost and arbuscular mycorhiza fungi. This system will create environmental friendly agriculture or agricultural system focusing on utilizing biological manure which can improve land productivity. Experiment was arranged in completely randomized design with two treatment factors and three replicated . First factor is type of compost, municipal waste compost , cow manure compost, chicken manure compost.. Second factor is doses of mycorhizal fungi, without mycorhiza ,5 g /plant, 10 g/plant,15 g/plant and 20 g./plant. The results showed that (1) there was significant interaction effect between compost and mycorrhizal fungi on growth and yield of soybean under water stress conditions, (2) plant height and root dry weight were significantly affected by different type of compost and mychorrhizal dose., (3) Different type of compost gave significant effect on number of branch and shoot dry weight, and (4) Applying different dose of mychorrhizal fungi would significantly affect number of pods and number of filled pods of soybean crop. Key word : Mycocompost, water,stress, manure